Screening method for the simultaneous determination of allantoin and uric acid from dried blood spots - Kopčil, Michal; Kanďár, Roman (Elsevier Science Inc., 2023)
Uric acid and its oxidation product allantoin are excellent biomarkers of oxidative stress in humans. Currently, there are high requirements not only for tests monitoring oxidative stress but also for screening laboratory tests in general. The highest demand is imposed on the simplest sampling, easy transport of the sample, and the shortest possible analysis time. The possible solution how to fulfil the requirements is sampling by dried blood spot technique with subsequent HPLC-MS/MS analysis. A fast, sensitive, and reliable HPLC-MS/MS method for the simultaneous determination of uric acid and allantoin from dried blood spots using stable isotopically labelled analogs as internal standards was developed. The separation took place in the reversed phase within 3 min, with protein precipitation and extraction in a one-step procedure. The analytical parameters of the method were satisfactory with an excellent linear range. The presented method was used to determine allantoin and uric acid levels in dried blood spot samples from 100 healthy volunteer donors. The median uric acid concentration in the cohort was 239.3 mu mol/L and the median allantoin concentration was 5.6 mu mol/L. The presented analytical protocol and method are suitable for screening and monitoring allantoin and uric acid levels as biomarkers of oxidative stress in clinical practice.
Screeningová metoda pro simultánní stanovení alantoinu a kyseliny močové ve vzorcích suché kapky krve
Keywords: Allantoin; Dried blood spot; Liquid chromatography; Tandem mass spectrometry; Uric acid; Oxidative stress; alantoin; suchá kapka krve; kapalinová chromatografie; tandemová hmotnostní spektrometrie; kyselina močová; oxidativní stres